Application of Moderate Alms to Improve Social Welfare of the Community - Rifqi Lidzikrirrofiqi, Muhammad; Anwar, Syahrul; Kania, Dede (Zona Law And Public Administration Indonesia, 2024)
The social welfare of the community is an important indicator in measuring the level of success of a community. within the framework of islamic teachings, almsgiving has been upheld as a principle of providing assistance to those in need. however, in this modern era, the concept of moderate almsgiving has emerged as a response to complex social and economic dynamics. this research utilizes the desk research method, which involves collecting data from scientific papers and other relevant library materials. the researcher conducted in-depth analyses of sources such as books, scientific journals, statistical references, theses, dissertations, and other internet sources. before conducting the analysis, the researcher ensured that the sources of scientific information were obtained from reliable sources and were relevant to the topic of the research. moderate religion also has the power to change the paradigm of society from indifference to care and from greed to generosity. it creates a social environment where empathy and care become key drivers in shaping public policy and helping those less fortunate. moderate almsgiving is not just about giving but also about empowering. by understanding the needs of fellow human beings and providing relevant support, people can form strong and empowered communities. when the principles of moderate almsgiving are applied with wisdom and sustainability, they create an environment where social justice is not a dream but a realizable reality